Enhancement in IEEE 1500 standard for at-speed functional testing - Ali, G. (IEEE Computer Society, 2014)
System on chip (SOC) makes it possible to design a complex system in a short period of time by using intellectual property (IP) blocks. The complexity of the design makes testing of the SOC a very difficult task. To alleviate this test access issue, IEEE 1500 has been introduced. It has become a widely used option because of its completeness and easy to use approach, but this standard is only supported in the test mode as it stays transparent in normal functional mode. In this paper, an enhancement of the existing IEEE 1500 standard for functional testing, during functional mode of operation, is proposed. Â© 2014 IEEE.